Optimalisasi Kompetensi Tutor melalui Penyusunan Silabus dan Pembagian Tugas Berbasis Talkshow Edukatif di PKBM SYIFA - Astoko, Dudi Budi; Fatchurrahman, Muhammad; Praptiningsih, Praptiningsih; Abbas, Ngatmin (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program enhanced the pedagogical and professional competencies of non-formal education tutors, especially those at Community Learning Activity Centers (PKBM), to meet 21st-century learning demands. Because PKBM tutors must go beyond content mastery, the program emphasized communicative, reflective, and contextually relevant teaching. Using a participatory-reflective approach, it was delivered through an interactive educational talk show, guided discussions, and collective reflection at Hotel Grand Amira, Surakarta. Implementation followed three stages: preparation, execution, and reflection–evaluation. Results showed improved understanding of active learning principles, stronger reflective awareness in teaching practice, and increased motivation to adopt innovative and humanistic strategies. The activity also strengthened tutors’ professional networks and fostered a culture of sharing best practices within the PKBM environment. Overall, the educational talk show model is an effective and sustainable alternative for developing non-formal tutor competencies and supporting quality learning services.